Notch fatigue analysis and crack initiation life estimation of maraging steel fabricated by laser beam powder bed fusion under multiaxial loading. (December 2021) - Branco, R.; Prates, P.A.; Costa, J.D.; Martins Ferreira, J.A.; Capela, C.; Berto, F.
Highlights: Cyclic plasticity at the notch was simulated via an isotropic-kinematic hardening model. Crack initiation sites and crack angles were predicted from the first principal stress. Un-melted regions were the main cause of fatigue crack initiation at the notch zone. Multiaxial fatigue life was predicted by combining a SWT-based model with the TCD. Abstract: This paper deals with the notch fatigue behaviour and crack initiation life estimation in maraging steel fabricated by laser beam powder bed fusion under multiaxial loading. Tests are conducted in tubular geometries with lateral holes considering different normal stress to shear stress ratios and multiaxial loading levels. The cyclic stress–strain response at the notch-controlled process zone is simulated numerically using two alternative approaches: a generalised isotropic plasticity model with mixed isotropic-kinematic hardening, and a linear-elastic model. Both approaches demonstrated to be suitable for predicting the crack initiation sites, the directions of crack growth, and the fatigue life. Fatigue life was calculated from a SWT-based model combined with the Theory of Critical Distances. Elastic-plastic predictions led to smaller errors but slightly shifted to the non-conservative side.